2002
DOI: 10.1002/bip.10201
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and collagen catabolism

Abstract: The matrix metalloproteinase (MMP)/matrixin family has been implicated in both normal tissue remodeling and a variety of diseases associated with abnormal turnover of extracellular matrix components. The mechanism by which MMPs catabolize collagen (collagenolysis) is still largely unknown. Substrate flexibility, MMP active sites, and MMP exosites all contribute to collagen degradation. It has recently been demonstrated that the ability to cleave a triple helix (triple-helical peptidase activity) can be disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
156
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(162 citation statements)
references
References 101 publications
2
156
0
4
Order By: Relevance
“…It has been reported that local fluctuations in the triple helical stability may play a role in the interactions of collagens and other proteins, such as matrix metalloproteases (43). So far, the imino acid content of a particular sequence stretch has been the main factor used in such considerations, but it is known that collagenase labile stretches contain a very low content of charged residues (44,45). The results presented here suggest that the lack of salt bridges in those regions may provide a complementary destabilization strategy.…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that local fluctuations in the triple helical stability may play a role in the interactions of collagens and other proteins, such as matrix metalloproteases (43). So far, the imino acid content of a particular sequence stretch has been the main factor used in such considerations, but it is known that collagenase labile stretches contain a very low content of charged residues (44,45). The results presented here suggest that the lack of salt bridges in those regions may provide a complementary destabilization strategy.…”
Section: Discussionmentioning
confidence: 78%
“…Several features of the cleavage site have been shown to contribute to MMP specificity, including the distribution of secondary amino acids (Pro and Hyp), dynamics of the peptide backbone, and overall lack of charged residues (with the primary exception of the P 5 Ј and P 8 Ј subsites) (1,5,24,31). The interaction of MMPs with triple helices encompasses at least the P 13 -P 17 Ј subsites (26,27,29,60).…”
Section: Discussionmentioning
confidence: 99%
“…Features of the MMP cleavage site in interstitial collagens have been investigated through a variety of approaches, including (a) kinetic analyses of MMP hydrolysis of native and mutant collagens and triple-helical peptide (THP) models of collagen, (b) biophysical studies (NMR spectroscopy and x-ray crystallography) of THPs, and (c) molecular dynamics simulations of triple helices (6 -30). It has been noted that, although collagen has a significant distribution of charged residues, relatively few are found at the site of MMP hydrolysis (5,31). More specifically, the overall 25-amino acid residue region surrounding the site of hydrolysis (subsites P 13 -P 12 Ј) contains a maximum of two charged residues (Glu in the P 8 subsite of the ␣1(II) chain, Arg in the P 5 Ј subsite of the ␣1(I) and ␣1(II) chains, and Arg in the P 8 Ј subsite of the ␣1(III) chain).…”
mentioning
confidence: 99%
“…Collagenolysis by interstitial collagenase is dependent on the hemopexin domain and linker peptide (12). Gelatinolysis by gelatinases is more than 100-fold enhanced by the gelatin-binding fibronectin domain (13).…”
mentioning
confidence: 99%